Contribution of Nepal Telecom to Nepalese Revenue - Gautam, Biranji; Sharma, Devi Lal (Janapriya Journal of Interdisciplinary Studies, 2020)
Public enterprise in Nepal plays vital role in generating revenue in Nepal. Nepal Telecom (NT) is the leading and high revenue contributing public enterprise in Nepal. The main aim of this study is to examine the contribution of different tax from NT to Nepalese revenue. Hence, descriptive research design was applied to complete this study. Under the descriptive research design case study of NT has carried out to attain the desired objective of this study. At present there are major five licensed mobile telecom are into operation in Nepal which was considered as population. Out of these, NT has coverage nationwide as well highest revenue generating company. So, NT is taken as sample by following the convenience sampling method. The study has based on secondary data. Revenue from NT includes income tax, and VAT, custom, service fees, local development fees, dividend tax, and share of profit etc. The income tax from NT to total revenue is the highest 1.66 percent and the least 1.19 percent and average 1.43 percent during the study period